Modulating neuronal competition dynamics in the dentate gyrus to rejuvenate aging memory circuits - McAvoy, Kathleen M.; Bartsch, Dusan (Neuron, 2016)
Summary: The neural circuit mechanisms underlying the integration and functions of adult-born dentate granule cell (DGCs) are poorly understood. Adult-born DGCs are thought to compete with mature DGCs for inputs to integrate. Transient genetic overexpression of a negative regulator of dendritic spines, Kruppel-like factor 9 (Klf9), in mature DGCs enhanced integration of adult-born DGCs and increased NSC activation. Reversal of Klf9 overexpression in mature DGCs restored spines and activity and reset neuronal competition dynamics and NSC activation, leaving the DG modified by a functionally integrated, expanded cohort of age-matched adult-born DGCs. Spine elimination by inducible deletion of Rac1 in mature DGCs increased survival of adult-born DGCs without affecting proliferation or DGC activity. Enhanced integration of adult-born DGCs transiently reorganized adult-born DGC local afferent connectivity and promoted global remapping in the DG. Rejuvenation of the DG by enhancing integration of adult-born DGCs in adulthood, middle age, and aging enhanced memory precision.